CPNE2: A NEW REGULATOR OF LYSOSOMAL-MITOCHONDRIAL FUNCTION INVOLVED IN AGING AND DISEASE. (11th November 2018) - Coppotelli, G; Ross, J; Ling, A; Kim, K; Sinclair, D
Abstract: Mitochondria play a critical role in maintaining cellular homeostasis by regulating cellular bioenergetics as well as calcium levels, apoptosis, and inflammation. Since mitochondrial dysfunction is a hallmark of aging, we performed a high-throughput in vitro screen of the human genome for candidate longevity genes based on correlates of aging with mitochondrial function as a primary readout. We identified 94 hits, and after secondary screening and differential RNA-seq analysis of young vs. old mouse muscle, CPNE2 emerged as the top candidate. CPNE2 belongs to a family of calcium-dependent phospholipid binding proteins, and apart from their ability to translocate to membranous compartments upon calcium signaling their function remains unknown. Our data indicate that CPNE2 silencing in myoblasts affects autophagosome clearance while increasing lysosomial mass and cathepsin B activity. In addition, GWAS analysis identified single nucleotide polymorphism variants within the CPNE2 open reading frame that are significantly associated with AD incidence. To verify the role of CPNE2 as a key regulator of mitochondrial and lysosomal function during aging, possibly affecting cognition and brain function, we have generated the first CPNE2 KO mouse. The mouse expresses LacZ protein under the CPNE2 promoter. CPNE2 KO mice are viable and LacZ expression reveals that CPNE2 is ubiquitously expressed with high levels present in the brain, particularly in cerebellum and ependymal cells. Work is in progress to characterize the CPNE2 knockout mice in order to elucidate the precise role of CPNE2 at the interface between autophagy, lysosomes, and mitochondria in the context of normal aging and disease.